PENGARUH LATIHAN PILATES TERHADAP KELELAHAN IBU PADA MASA NIFAS - Riana Pascawati; Yulidar Yanti; Dewi Purwaningsih (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2021)
Fatigue is a common symptom experienced during the postpartum period with up to 67% of women reporting severe fatigue at 12 months after delivery. Side affects of postpartum fatigue can affect the lactation process, decreased sexual intercourse between partners, stress and mood disorders and an increased of postpartum depression. In general, an effective strategy to reduce the effects of fatigue during the puerperium is pilates exercises during postpartum. Pilates exercises are effective because they are easy and can be done at home. The general objective in this study was to analyze the effect of pilates exercise on maternal fatigue during the postpartum period. This study used a one group pre-post test design. The population of this study were all post-partum mothers in the work area of ​​Garuda Primary Health Center, Bandung City. The number of samples according to the inclusion criteria was 20 respondents. Sampling in this study was conducted using consecutive sampling technique. Data analysis using dependent t-test. The results show that all respondents were in the healthy reproductive age range between 20-27 years. EPDS scores ranged from 2-9 and BMI was in the normal category. There was a decrease in the fatigue score after 4 weeks of pilates exercise with an average decrease in the FAS score of 10.5. There is an effect of pilates exercise on fatigue during postpartum with a p value = 0.001. Based on the results of this study, it is hoped that midwives can routinely provide pilates exercise care to mothers and it was an effective step in the efforts of maternal and infant health.